2016
DOI: 10.2217/fon.16.22
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rare Germline Copy Number Variation in Melanoma-Prone Patients

Abstract: Patients harboring rare CNVs exhibited a decreased age of disease onset, in addition to an overall higher skin cancer predisposition. Our findings suggest that rare CNVs contribute to melanoma susceptibility, and should be taken into account when investigating cancer risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Previous studies revealed that histone family genes are involved in multiple cancer types. Copy number variations of HIST1H1B were reported to be associated with cellular development and growth, and with proliferation in melanoma (30). HIST1H3B , as an amplification-dependent driver oncogene, was reported to be overexpressed in liver cancer (31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that histone family genes are involved in multiple cancer types. Copy number variations of HIST1H1B were reported to be associated with cellular development and growth, and with proliferation in melanoma (30). HIST1H3B , as an amplification-dependent driver oncogene, was reported to be overexpressed in liver cancer (31).…”
Section: Discussionmentioning
confidence: 99%
“…In this workflow, the gene list submitted to VarElect includes genes residing (completely or partially) within the detected SVs. This mode of analysis using VarElect helped solve a number of cases (Homma et al 2018;Fidalgo et al 2016). One study aimed to diagnose recurrent CNVs associated with syndromic short stature of unknown cause (Homma et al 2018).…”
Section: Interpretation Of Genomic Structural Variants (Svs)mentioning
confidence: 99%
“…Germline CNVs are a class of structural variations, and are defined as loss or gain of genomic DNA in size range of 50 bp to 1 Mb 14 . Germline CNVs are studied as genetic determinants for susceptibility for familial breast cancer 15 20 and also cancers of prostate 21 23 , ovary 18 , 24 26 , pancreas 27 29 , colon, rectum 16 , 30 – 34 , endometrium 35 , lung 36 38 and melanoma 39 , 40 .…”
Section: Introductionmentioning
confidence: 99%